Influence of Organization-Public Relationship Practices on Organization Effectiveness in Jordanian Public Hospitals - Al-Adwan, Muhammad Noor Saleh (2013)
Nowadays, public relations is seen as an important part which helps an organization in bridging the gap with its public so that the mutual relationship is established. Most previous research on Organization-Public Relationship (O-PR) investigate the relationship from an organizational perspective, where as this research investigate from the customers’ perspectives. Previous research done in the western world show that the practices of trust, commitment, community involvement, openness, and customers’ satisfaction are attributes towards types of O-PR practice (personal, professional and community). However, literature seems to suggest that much research work is needed to better understand such attributes especially from the public relations practices in Arab country. This study is pursued to elicit the importance of O-PR and it type of practices towards organizational effectiveness in sustaining organizational image, identity, and reputation. The questionnaires were distributed to 600 patients at a major hospital in Jordan with 94.8% response rate. The research findings show significant relationships between O-PR practices and type of relationships with organizational effectiveness (image, identity and reputation). In predicting best practice of O-PR, the study elicited that commitment and patient satisfaction were shown to have the strongest contributions in O-PR as compared to previous research in western countries. Based on the type of relationships practices, personal relationship practice provides the strongest contribution towards organizational image, identity and reputation. The finding of this research will help public relation practitioners in the planning of strategic relationship management in developing best practices of O-PR. The need for improvement in this area requires serious attention especially the practices of commitment and satisfying customer satisfaction. Conclusions as to the impact of public relations as relationship management of organisation-public are offered, as well as suggestions for future areas of research.